More than you wanted to know : the failure of mandated disclosure - Ben-Shahar, Omri; Schneider, Carl, 1948- (Princeton University Press, 2014)
Perhaps no kind of regulation is more common or less useful than mandated disclosure-requiring one party to a transaction to give the other information. It is the iTunes terms you assent to, the doctor's consent form you sign, the pile of papers you get with your mortgage. Reading the terms, the form, and the papers is supposed to equip you to choose your purchase, your treatment, and your loan well. More Than You Wanted to Know surveys the evidence and finds that mandated disclosure rarely works. But how could it? Who reads these disclosures? Who understands them? Who uses them to make better choices?